2018
DOI: 10.1016/j.prro.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Determining the impact of pre-radiation treatment verification simulation/dry run by analyzing intradepartmental reported incidents and surveying staff and patients

Abstract: A VS helps identify and correct incidents before the administration of radiation therapy and reduces patient anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In addition to the HCT simulation, all patients also underwent a verification simulation (i.e., a “dry run”) on the treatment machine the day before their first fraction of treatment. This verification session duplicates the steps of patient setup, imaging, and treatment without actually delivering the radiation, which allows staff time to verify the isocenter placement, check geometric clearance and troubleshoot potential problems in an organized team approach 10 . All patients were treated with a 4–5 fractions schedule that delivered over 1–2 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the HCT simulation, all patients also underwent a verification simulation (i.e., a “dry run”) on the treatment machine the day before their first fraction of treatment. This verification session duplicates the steps of patient setup, imaging, and treatment without actually delivering the radiation, which allows staff time to verify the isocenter placement, check geometric clearance and troubleshoot potential problems in an organized team approach 10 . All patients were treated with a 4–5 fractions schedule that delivered over 1–2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…This verification session duplicates the steps of patient setup, imaging, and treatment without actually delivering the radiation, which allows staff time to verify the isocenter placement, check geometric clearance and troubleshoot potential problems in an organized team approach. 10 All patients were treated with a 4-5 fractions schedule that delivered over 1-2 weeks. 4D CBCT images were acquired for image guidance during the verification session and prior to each treatment delivery using the Elekta XVI Symmetry™ protocol.…”
Section: Patient Selection and Conventional Registration Methodsmentioning
confidence: 99%
“…This process is performed with the help of computers to simulate the patient's anatomy and cancer location, for both practice and quality assurance purposes [11]. A study conducted in 2018 confirmed that this process resulted in reduction in the rate of incidents during treatment and anxiety levels of both patients and staff during treatment [12]. After patient setup and plan verification, the patient is finally ready to receive radiation treatment.…”
Section: The Radiotherapy Chainmentioning
confidence: 99%